2013
DOI: 10.1051/0004-6361/201321029
|View full text |Cite
|
Sign up to set email alerts
|

The open cluster IC 1805 and its vicinity: investigation of stars in the Vilnius, IPHAS, 2MASS, and WISE systems

Abstract: The results of CCD photometry in the Vilnius seven-color system down to V = 18 mag are presented for 242 stars in the direction of the young open cluster IC 1805 that is located in the active star-forming region W4 in the Cas OB6 association. Photometric data were used to classify stars into spectral and luminosity classes, and to determine their interstellar reddenings, extinctions and distances. We confirm the CH 3 OH and H 2 O maser VLBA parallax results that the cluster is located close to the front side o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In Simbad, it appears close to 2MASS J02324314+6130587 (which has a likely YSO classification in Broos et al 2013, and a class II YSO classification in Sung et al, in prep.). Straižys et al (2013) reported a WISE counterpart, suggesting this object to be an Ae/Be highmass YSO (see also Sect. 4.2).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In Simbad, it appears close to 2MASS J02324314+6130587 (which has a likely YSO classification in Broos et al 2013, and a class II YSO classification in Sung et al, in prep.). Straižys et al (2013) reported a WISE counterpart, suggesting this object to be an Ae/Be highmass YSO (see also Sect. 4.2).…”
mentioning
confidence: 88%
“…The optical/IR counterpart is a likely YSO ) lying in the PMS locus (Sung et al, in prep.). Straižys et al (2013) quoted a photometric spectral type G for this object.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For about 73% of stars, two-dimensional spectral types (spectral and luminosity classes) were determined applying two classification codes based on interstellar reddening-free Q-parameters. One of these codes, COMPAR, applies a comparison of Q-parameters of stars in the area and individual standard stars (Straižys et al 2013). The second code, now renamed to KLASQ, is described in Milašius et al (2013).…”
Section: Photometric Data and Spectral Typesmentioning
confidence: 99%
“…Bik et al (2012) suggest that W3-Main harbors several H II regions, ranging from very young hyper-compact H II regions (HCHfew 10 3 yr old) and ultra-compact H II regions (UCH-about 10 5 yr old) to more evolved, diffuse H II regions with ages of a few 10 6 yr (Wood & Churchwell 1989). The massive stars in IC 1805 have been characterized (e.g., Rauw & De Becker 2004;De Becker et al 2006;Rauw & Nazé 2016), along with multi-wavelength studies of the low and intermediate-mass population (e.g., Straižys et al 2013;Panwar et al 2017) and of the physics of the W4 super-bubble expansion (e.g., Basu et al 1999;Gao et al 2015). For the W5 complex, studies like those of Karr & Martin (2003) and Niwa et al (2009) discuss the expansion of the H II regions and the effects on cluster evolution.…”
Section: Introductionmentioning
confidence: 99%